Amorphous calcium phosphate reinforced alginate-dialdehyde-gelatin (ADA-GEL) bioink for biofabrication of bone tissue scaffolds - Indurkar, Abhishek; Heid, Susanne; Bauer, Julian; Rubenis, Kristaps; Friedrich, Oliver; Locs, Janis; Boccaccini, Aldo R. (Carbohydrate Polymer Technologies and Applications, 2025)
The aim of this work was to develop a nanocomposite bioink closely resembling the nanostructure of bone incorporating amorphous calcium phosphate (ACP) as an inorganic counterpart, specifically, citrate stabilized ACP (ACP_CIT) and non-stabilized ACP (ACP_ACE) in an organic hydrogel matrix consisted of alginate dialdehyde-gelatin (ADA-GEL). The hydrogel's physical properties were evaluated, confirming the reinforcement effect of ACP. The frequency sweep analysis showed that G' and G" of ADA-GEL were 99 ± 9 Pa and 9 ± 1 Pa, respectively. By the addition of ACP_ACE, G' and G" increased. Overall, the viscoelastic and mechanical properties of ADA-GEL hydrogel were enhanced by ACP. ACP_CIT was more effective than ACP_ACE. Further, printing parameters were optimized. The bioink was formulated by embedding MC3T3-E1 cells in ADA-GEL and ACP-reinforced ADA-GEL hydrogels, followed by fabricating scaffolds at optimized printing parameters (pressure: 65 kPa, speed: 5 mm/s). Crosslinking was performed by immersing constructs in CaCl2 and microbial transglutaminase solution. Post-printing analysis was performed using the printability index and average pore area analysis. The lowest structural stability was observed in ADA-GEL constructs. The highest structural stability was noted in ADA-GEL-ACP_CIT constructs. Epifluorescence and two-photon microscopy of Rhodamine/Phalloidin stained constructs confirmed the cytocompatibility of the bioinks.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Alginate dialdehyde-gelatin bioink; Bioprinting; Bone tissue engineering; Citrate stabilized amorphous calcium phosphate; Nanocomposite bioink

Assessment of Cell Viability in Electrically Excitable Muscle Cells Through Intact Twitch Stimulation - Bauer, Julian; Head, Stewart I.; Friedrich, Oliver (Cell Viability Assays (2nd Edt.), 2023)
Muscle cells (i.e. skeletal muscle fibers) are fully viable and functional when their excitation-contraction (EC) coupling machinery is intact. This involves intact membrane integrity with polarized membrane, functional ion channels for action potential generation and conduction, an intact electro-chemical interface at the level of the fiber’s triad, followed by sarcoplasmic reticulum Ca2+ release, and subsequent activation of the chemico-mechanical interface at the level of the contractile apparatus. The ultimate end result is then a visible twitch contraction upon a brief electrical pulse stimulation. For many biomedical studies involving single muscle cells, intact and viable myofibers are of utmost importance. Thus, a simple global screening method that involves a brief electrical stimulus applied to single muscle fibers and assessment of visible contraction would be of high value. In this chapter, we describe step-by-step protocols to (i) obtain intact single muscle fibers from freshly dissected muscle tissue using an enzymatic digestion procedure and (ii) provide a workflow for the assessment of twitch response of single fibers that can be ultimately classified as viable. For this, we have prepared a unique stimulation pen for which we provide the fabrication guide for do-it-yourself rapid prototyping to eliminate the need for expensive specialized commercial equipment.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Contraction; Electrical stimulator; Enzymatic dissociation; Single fiber; Skeletal muscle; Twitch stimulation

CAS3D: 3D quantitative morphometry on Second Harmonic Generation image volumes from single skeletal muscle fibers - Schneidereit, Dominik; Bauer, Julian; Mnuskina, Sofia; Nübler, Stefanie; Cacciani, Nicola; Mühlberg, Alexander; Kreiß, Lucas; Ritter, Paul; Schürmann, Sebastian; Larsson, Lars; Friedrich, Oliver (Computers in Biology and Medicine, 2024)
The CAS3D image processing method intuitively applies a combination of Fourier space and real space 3D analysis algorithms to volumetric images of single skeletal muscle fiber Myosin II Second Harmonic Generation (SHG) XYZ image data. Our developed tool automatically quantifies the myofibrillar orientation in muscle samples by determining the cosine angle sum of intensity gradients in 3D (CAS3D) while determining the mean sarcomere length (SL) and sample orientation. The expected CAS3D values could be reproduced from ideal artificial data sets. Applied random noise in artificial images lowers the detected CAS3D value, and for noise levels below 20%, the correlation can be approximated by a linear function with a slope of −0.006 CAS3D/noise%. The deviations in SL and orientation detection were determined on ideal and noisy artificial data sets and were statistically indistinguishable from 0 (null hypothesis t-test P > 0.1). The software was applied to a previously published data set of single skeletal muscle fiber volumetric SHG image data from a rat intensive care unit (ICU) model of ventilator-induced diaphragm dysfunction (VIDD) with treatment regimens involving the small anti-inflammatory molecules BGP-15, vamorolone, or prednisolone. Our method reliably reproduced the results of the previous work and improved the standard deviation of the cosine angle sum detection in all sample groups from a mean of 0.03 to 0.008. This improvement is achieved by applying analysis algorithms to the whole volumetric images in 3D in contrast to the previously common method of slice-wise XY analysis.
CRIS-Team Scopus Importer:2024-07-19
Keywords: 3D image analysis; Quantitative morphometry; Second harmonic generation; Skeletal muscle; Software automation

Myofibrillar Lattice Remodeling Is a Structural Cytoskeletal Predictor of Diaphragm Muscle Weakness in a Fibrotic mdx (mdx Cmah(-/-)) Model - Ritter, Paul; Nübler, Stefanie; Buttgereit, Andreas; Smith, Lucas R.; Mühlberg, Alexander; Bauer, Julian; Michael, Mena; Kreiß, Lucas; Haug, Michael; Barton, Elisabeth; Friedrich, Oliver (International Journal of Molecular Sciences, 2022)
Duchenne muscular dystrophy (DMD) is a degenerative genetic myopathy characterized by complete absence of dystrophin. Although the mdx mouse lacks dystrophin, its phenotype is milder compared to DMD patients. The incorporation of a null mutation in the Cmah gene led to a more DMD-like phenotype (i.e., more fibrosis). Although fibrosis is thought to be the major determinant of 'structural weakness', intracellular remodeling of myofibrillar geometry was shown to be a major cellular determinant thereof. To dissect the respective contribution to muscle weakness, we assessed biomechanics and extra- and intracellular architecture of whole muscle and single fibers from extensor digitorum longus (EDL) and diaphragm. Despite increased collagen contents in both muscles, passive stiffness in mdx Cmah(-/-) diaphragm was similar to wt mice (EDL muscles were twice as stiff). Isometric twitch and tetanic stresses were 50% reduced in mdx Cmah(-/-) diaphragm (15% in EDL). Myofibrillar architecture was severely compromised in mdx Cmah(-/-) single fibers of both muscle types, but more pronounced in diaphragm. Our results show that the mdx Cmah(-/-) genotype reproduces DMD-like fibrosis but is not associated with changes in passive visco-elastic muscle stiffness. Furthermore, detriments in active isometric force are compatible with the pronounced myofibrillar disarray of the dystrophic background.
CRIS-Team WoS Importer:2022-09-30

Partner, Neighbor, Housekeeper and Dimension: 3D versus 2D Glomerular Co-Cultures Reveal Drawbacks of Currently Used Cell Culture Models - Rederer, Anna; Rose, Victoria; Krüger, René; Schmittutz, Linda; Swierzy, Izabela; Fischer, Lena; Thievessen, Ingo; Bauer, Julian; Friedrich, Oliver; Schiffer, Mario; Müller-Deile, Janina (International Journal of Molecular Sciences, 2023)
Signaling-pathway analyses and the investigation of gene responses to different stimuli are usually performed in 2D monocultures. However, within the glomerulus, cells grow in 3D and are involved in direct and paracrine interactions with different glomerular cell types. Thus, the results from 2D monoculture experiments must be taken with caution. We cultured glomerular endothelial cells, podocytes and mesangial cells in 2D/3D monocultures and 2D/3D co-cultures and analyzed cell survival, self-assembly, gene expression, cell–cell interaction, and gene pathways using live/dead assay, time-lapse analysis, bulk-RNA sequencing, qPCR, and immunofluorescence staining. Without any need for scaffolds, 3D glomerular co-cultures self-organized into spheroids. Podocyte- and glomerular endothelial cell-specific markers and the extracellular matrix were increased in 3D co-cultures compared to 2D co-cultures. Housekeeping genes must be chosen wisely, as many genes used for the normalization of gene expression were themselves affected in 3D culture conditions. The transport of podocyte-derived VEGFA to glomerular endothelial cells confirmed intercellular crosstalk in the 3D co-culture models. The enhanced expression of genes important for glomerular function in 3D, compared to 2D, questions the reliability of currently used 2D monocultures. Hence, glomerular 3D co-cultures might be more suitable in the study of intercellular communication, disease modelling and drug screening ex vivo.
Created from Fastlane, Scopus look-up
Keywords: 3D co-culture; bulk-RNA sequencing; cell culture model; cell matrix; cell–cell communication; glomerular spheroids

Single fibre cytoarchitecture in ventilator-induced diaphragm dysfunction (VIDD) assessed by quantitative morphometry second harmonic generation imaging: Positive effects of BGP-15 chaperone co-inducer and VBP-15 dissociative corticosteroid treatment - Mnuskina, Sofia; Bauer, Julian; Wirth-Hücking, Anette; Schneidereit, Dominik; Nübler, Stefanie; Ritter, Paul; Cacciani, Nicola; Li, Meishan; Larsson, Lars; Friedrich, Oliver (Frontiers in Physiology, 2023)
Ventilator-induced diaphragm dysfunction (VIDD) is a common sequela of intensive care unit (ICU) treatment requiring mechanical ventilation (MV) and neuromuscular blockade (NMBA). It is characterised by diaphragm weakness, prolonged respirator weaning and adverse outcomes. Dissociative glucocorticoids (e.g., vamorolone, VBP-15) and chaperone co-inducers (e.g., BGP-15) previously showed positive effects in an ICU-rat model. In limb muscle critical illness myopathy, preferential myosin loss prevails, while myofibrillar protein post-translational modifications are more dominant in VIDD. It is not known whether the marked decline in specific force (force normalised to cross-sectional area) is a pure consequence of altered contractility signaling or whether diaphragm weakness also has a structural correlate through sterical remodeling of myofibrillar cytoarchitecture, how quickly it develops, and to which extent VBP-15 or BGP-15 may specifically recover myofibrillar geometry. To address these questions, we performed label-free multiphoton Second Harmonic Generation (SHG) imaging followed by quantitative morphometry in single diaphragm muscle fibres from healthy rats subjected to five or 10 days of MV + NMBA to simulate ICU treatment without underlying confounding pathology (like sepsis). Rats received daily treatment of either Prednisolone, VBP-15, BGP-15 or none. Myosin-II SHG signal intensities, fibre diameters (FD) as well as the parameters of myofibrillar angular parallelism (cosine angle sum, CAS) and in-register of adjacent myofibrils (Vernier density, VD) were computed from SHG images. ICU treatment caused a decline in FD at day 10 as well as a significant decline in CAS and VD from day 5. Vamorolone effectively recovered FD at day 10, while BGP-15 was more effective at day 5. BGP-15 was more effective than VBP-15 in recovering CAS at day 10 although not to control levels. In-register VD levels were restored at day 10 by both compounds. Our study is the first to provide quantitative insights into VIDD-related myofibrillar remodeling unravelled by SHG imaging, suggesting that both VBP-15 and BGP-15 can effectively ameliorate the structure-related dysfunction in VIDD.
CRIS-Team Scopus Importer:2023-08-25
Keywords: BGP-15; critical illness; diaphragm dysfunction; quantitative morphometry; second harmonic generation

Vascularization of Poly-ε-Caprolactone-Collagen I-Nanofibers with or without Sacrificial Fibers in the Neurotized Arteriovenous Loop Model - Kratzer, Simon; Arkudas, Andreas; Himmler, Marcus; Schubert, Dirk W.; Schneidereit, Dominik; Bauer, Julian; Friedrich, Oliver; Horch, Raymund E.; Cai, Aijia (Cells, 2022)
Electrospun nanofibers represent an ideal matrix for the purpose of skeletal muscle tissue engineering due to their highly aligned structure in the nanoscale, mimicking the extracellular matrix of skeletal muscle. However, they often consist of high-density packed fibers, which might impair vascularization. The integration of polyethylene oxide (PEO) sacrificial fibers, which dissolve in water, enables the creation of less dense structures. This study examines potential benefits of poly-ε-caprolactone-collagen I-PEO-nanoscaffolds (PCP) in terms of neovascularization and distribution of newly formed vessels compared to poly-ε-caprolactone -collagen I-nanoscaffolds (PC) in a modified arteriovenous loop model in the rat. For this purpose, the superficial inferior epigastric artery and vein as well as a motor nerve branch were integrated into a multilayer three-dimensional nanofiber scaffold construct, which was enclosed by an isolation chamber. Numbers and spatial distribution of sprouting vessels as well as macrophages were analyzed via immunohistochemistry after two and four weeks of implantation. After four weeks, aligned PC showed a higher number of newly formed vessels, regardless of the compartments formed in PCP by the removal of sacrificial fibers. Both groups showed cell influx and no difference in macrophage invasion. In this study, a model of combined axial vascularization and neurotization of a PCL-collagen I-nanofiber construct could be established for the first time. These results provide a foundation for the in vivo implantation of cells, taking a major step towards the generation of functional skeletal muscle tissue.<br
Keywords: vascularization of nanofiber scaffolds; neurotization; neoangiogenesis; EPI loop model; AV loop model; PCL-collagen I-nanofiber scaffolds; polyethylene oxide